TRUST IN E-COMMERCE: HOW REVIEWS AND RATINGS SHAPE CONSUMER CONFIDENCE - Purnawati, Elisa (Management Studies and Business Journal (PRODUCTIVITY), 2024)
The rapid growth of e-commerce has transformed consumer shopping behavior; however, building consumer trust remains a major challenge, particularly in relation to product reviews and ratings. This study aims to analyze the role of online reviews and ratings in shaping consumer trust on e-commerce platforms, with a specific focus on identifying key factors that influence consumers' decision-making processes. Using a Systematic Literature Review (SLR) approach, this research analyzed 68 relevant articles published between 2015 and 2024. The findings reveal that review quality, volume, consistency, and reviewer credibility significantly influence consumer trust. Negative reviews tend to have a stronger impact than positive ones, while demographic and psychological factors moderate these effects. This study provides practical recommendations for e-commerce platforms to develop more transparent and credible review systems in order to enhance consumer trust.